2009
DOI: 10.1152/japplphysiol.00363.2009
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and long-term hypoxia alters Ca2+-induced Ca2+release in sheep cerebrovascular sympathetic neurons

Abstract: The contribution of sympathetic nerves arising from the superior cervical ganglia (SCG) toward the growth and function of cerebral blood vessels is pertinent throughout maturation as well as in response to cardiovascular stress imposed by high-altitude long-term hypoxia (LTH). The function of SCG sympathetic neurons is dependent on intracellular Ca2+ concentration ([Ca2+]i) signaling, which is strongly influenced by a process known as Ca2+-induced Ca2+ release (CICR) from the smooth endoplasmic reticulum (SER)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Notably, we have shown that caffeine elicits Ca 2ϩ responses in nearly all PA myocytes from fetal sheep, and the events have greater amplitude compared with adults (8). This also occurs in superior cervical ganglion neurons from these fetal sheep (1). Together, these findings provide support that RyRs are functional in utero in sheep PA myocytes and that their function may change following birth.…”
supporting
confidence: 61%
“…Notably, we have shown that caffeine elicits Ca 2ϩ responses in nearly all PA myocytes from fetal sheep, and the events have greater amplitude compared with adults (8). This also occurs in superior cervical ganglion neurons from these fetal sheep (1). Together, these findings provide support that RyRs are functional in utero in sheep PA myocytes and that their function may change following birth.…”
supporting
confidence: 61%
“…Interestingly, there is evidence of successful high‐altitude long‐term hypoxia acclimatization, with increases in carotid blood blow and no compromise in cerebral oxygenation . However, this adaptation is correlated with a significant intra‐uterine growth restriction and altered vascular functions . Moreover, the responses to high‐altitude long‐term hypoxia may effectively program cerebrovascular diseases at adulthood as vascular development and function require a finely controlled environment .…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, chronic hypoxia decreased cerebrovascular nNOS abundance, due presumably to decreased innervation by nitridergic nerves, particularly in immature arteries [116]. Ex vivo neurophysiological studies also demonstrated that chronic hypoxia can markedly attenuate calcium-induced calcium release, SERCA function, and subsequent norepinephrine release in fetal sympathetic neurons [117]. …”
Section: The 2000s: Calcium Cgmp Pkc and Fetal Cbfmentioning
confidence: 96%